Questionnaire for the Evaluation of Knowledge and Attitudes of Undergraduate Dentistry Students Regarding the Use of CAD-CAM in Class 2 Inlay Restoration Applications - Rahime Zeynep Erdem; Kevser Karakaya (Current Research in Dental Sciences, 2025)
Objective: This study aims to assess the knowledge and practices of undergraduate dental students regarding the use of CAD-CAM technology in inlay restorations for maxillary premolars affected by Class 2 caries.Methods: The questions used in this study were adapted from a previous survey and were translated into Turkish. The questionnaire, comprising 17 questions related to CAD-CAM knowledge, preferences, and group characteristics, was distributed to students in the 1st, 2nd, 3rd, 4th, and fifth years of dental education. Participants who volunteered and completed the entire questionnaire were included in the study, resulting in a total of 365 participants (272 preclinical and 93 clinical students).Results: In our study, the distribution by academic year was as follows: 75% were preclinical students, and 25% were clinical students. An analysis of the number and percentage of responses to the questions in the questionnaire, grouped by preclinical and clinical years as well as the total number of students, indicated significant differences between the groups in all questions except for S1 (Do you consider occlusion to be important?), S2 (What type of composite do you prefer for Class 2 restorations?), and S9 (In which cavities can indirect inlay restorations be preferred?).Conclusion: The findings suggest that practical education in CAD-CAM technology has yet to be fully integrated into undergraduate dental education; however, there is increasing awareness of its importance and a high level of interest among students for further education in this field.